Correlation between myocardial perfusion imaging findings and future cardiac events in patients with type 2 diabetes mellitus - Stanković Siniša (Serbian Medical Society, 2021)
Introduction/Objective. Myocardial perfusion imaging (MPI) is clinically useful for the evaluation of coronary artery disease in patients with diabetes mellitus. However, the prevalence of ischemia and its ability to predict future cardiac events is less clear. The aim was to determine the incidence of cardiac events in diabetic patients and the relationship between them and MPI findings. Methods. Two cohorts of patients, 98 diabetics and 100 non-diabetics, with medium- to high-risk of coronary artery disease without previous coronary revascularization, were studied prospectively. All of them were outpatients who underwent 99mTc-sestamibi MPI with dipyridamole. The data about cardiac events were collected during a follow-up period of two years. Results. Cardiac events occurred in 17.3% diabetics and in 8% non-diabetics (p = 0.048). Diabetics had shorter estimated event-free time of 24.7 months (95% CI 23.2–26.2) versus non-diabetics’ estimated event-free time of 28.5 months (95% CI 27.4–29.5) (p = 0.046). The independent predictors of cardiac events were male sex (p = 0.010), previous myocardial infarction (p < 0.001), presence of the symptoms of angina (p = 0.014), and all variables derived from MPI findings. After adjustment for variables derived from MPI findings, the significant predictors in diabetics were the size of stress perfusion defect (p = 0.022), summed stress score (p = 0.011), and summed difference score (p = 0.044). Conclusion. In diabetic patients, the cumulative rate of cardiac events was higher and the event-free survival was worse. MPI could help in prediction of cardiac events in diabetics and the most important predictors were size of stress perfusion defect, summed stress score, and summed difference score.